Studi Living Qur’an: Tradisi Pembacaan Surat Al-Waqi’ah Di Pondok Pesantren Darul-Falah Tulungagung - Salafudin, Ahmad Basith (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThis paper discuss the tradition of reading Surah al-Waqi’ah which is familiarly practiced at the Darul-Falah Islamic Boarding School in Tulungagung. In this pesantren, all students are required to follow this routine tradition so that they are accustomed to practicing it in their daily life. By using the Living Qur'an study and Karl Mannheim's approach in the analysis form of a problem by reviewing it from the point of view of objective, expressive, and documentary meanings, this paper draws the following conclusions; first, the tradition of Surah al-Waqi’ah is read regularly every day to motivate the reader to get so much fadhilah. Second, the objective meaning of the reading of Surah al-Waqi’ah, is that this tradition has been lived and rooted for a long time to make students as pious and 'alim students. Meanwhile, the expressive meaning of reading surah al-Waqi’ah, can provide relief in times of difficulty, ease in solving problems, and easy to obtain sustenance. As for the documentary meaning, it can make students become disciplined people in religion, especially those related to God (hablun minallah) and also with fellow humans (hablun minannas). AbstrakTulisan ini mengkaji tradisi pembacaan surat al-Waqi’ah yang familiar dipraktikkan di Pondok Pesantren Darul-Falah Tulungagung. Di pesantren ini, seluruh santri diwajibkan untuk mengikuti tradisi rutin tersebut agar terbiasa mengamalkannya dalam kehidupan keseharian. Dengan menggunakan studi Living Qur’an dan pendekatan Karl Mannheim, yakni menganalisis sebuah problem dengan meninjau dari sisi makna objektif, ekspresif dan dokumenter. Tulisan ini menghasilkan kesimpulan sebagai berikut; pertama, tradisi surat al-Waqi’ah dibaca secara rutin setiap hari untuk memotivasi pembaca agar mendapatkan fadhilah yang sangat banyak di dalamnya. Kedua, makna objektif dari pembacaan surat al-Waqi’ah ini, bahwa tradisi tersebut sudah dijalani dan mengakar sejak lama dengan tujuan menjadikan santri sebagai anak didik yang saleh dan ‘alim. Sementara makna ekspresif dari membaca surat al-Waqi’ah ini, dapat memberikan keringanan saat kesulitan, kemudahan dalam menyeleseikan masalah, dan gampang dalam memperoleh rezeki. Adapun makna dokumenternya, dapat membuat santri menjadi orang yang disiplin dalam beragama, khususnya yang berkaitan dengan Allah (hablun minallah) maupun juga dengan sesama manusia (hablun minannas). Kata Kunci: Al-Waqi’ah; Living Qur’an; PonPes Falah.